Standard Tests and Non-Standard Tests - Heriyanto, Heriyanto; Ayyobi, Iqbal; Rahmi, Citra Aulia; Erimawahti, Erimawahti; Marsela, Eva (Lembaga Riset Mutiara Akbar, 2025)
Assessment plays a crucial role in education by measuring the success of the teaching and learning process. One of the most common assessment tools used is tests, which can be categorized into two main types: standardized tests and non-standardized tests (teacher-made tests). Standardized tests are designed by expert teams with strict procedures to ensure validity and reliability, and they are used to compare student performance across different schools or educational institutions. In contrast, non-standardized tests are created by teachers to assess student achievement within a more specific and flexible context. This study aims to compare both types of tests in terms of their construction, implementation, and benefits in education. The research employs a comparative approach using literature review and field observations in several schools. The findings suggest that standardized tests offer advantages in consistency, validity, and the application of broad norms, while non-standardized tests are more flexible and tailored to the specific needs of a classroom. Both types of tests have distinct benefits, and the choice of which test to use should align with the intended evaluation goals.